Missing Persons: Cherokee's Parrot and Chatterton's Poet - Leonard R. Koos (Studies in 20th & 21st Century Literature, 1999)
This essay explores the problematic nature of selfhood in the detective genre as established by Edgar Allan Poe's "Murders in the Rue Morgue" (1841) and most recently reformulated in two metaphysical detective novels, Jean Echenoz's Cherokee (1983) and Peter Ackroyd's Chatterton (1987). Poe's detective Auguste Dupin is described as having a "Bi-Part Soul," which permits him to vacate himself in order to construct the narrative solution to a crime. This duality, in the postmodern detective novel, is transformed into an irrevocable dislocation of the subject. Cherokee's onomastic devalorization of the story's characters and simulation of the human subject in the figure of the parrot Morgan create an indeterminacy that renders traditional conceptions of the self obsolete or irrelevant. Chatterton, whose point of departure is the infamous eighteenth-century "forger" Thomas Chatterton, uses the issue and example of pastiche to problematize the notion of the constitution of a subject in language and time. Both Cherokee and Chatterton take advantage of the subjective presuppositions of the detective genre in order to delineate the intricate problems of selfhood as a postmodern concern.
Keywords: Edgar Allan Poe; Murders in the Rue Morgue; metaphysical detective novel; novel; metaphysical; Jean Echenoz; Cherokee; Peter Ackroyd; Chatterton; duality; postmodern; subject; time; space; delineation; selfhood; self